A Tree-Like Model for Brain Growth and Structure. (2nd September 2013) - Yan, Benjamin C.; Yan, Johnson F.
Abstract : The Flory-Stockmayer theory for the polycondensation of branched polymers, modified for finite systems beyond the gel point, is applied to the connection (synapses) of neurons, which can be considered highly branched "monomeric" units. Initially, the process is a linear growth and tree-like branching between dendrites and axons of nonself-neurons. After the gel point and at the maximum "tree" size, the tree-like model prescribes, on average, one pair of twin synapses per neuron. About 13% of neurons, "unconnected" to the maximum tree, migrate to the surface to form cortical layers. The number of synapses in each neuron may reach 10000, indicating a tremendous amount of flexible, redundant, and neuroplastic loop-forming linkages which can be preserved or pruned by experience and learning.